A National Survey of the Writing Instructional Practices of Teachers of Students With Visual Impairments - Michael Hebert; Derek B. Rodgers
Despite the importance of writing skill development, we know very little about how writing instruction is provided to students with visual impairments (VI) with and without co-occurring disabilities (e.g., multiple disabilities, deaf-blindness). The purpose of this study was to survey a national sample of U.S. teachers of students with visual impairments (TSVIs) on several important constructs, including their preparation to teach writing; their beliefs, attitudes, and experiences about teaching writing; and the writing practices they use for students with various visual conditions. We received responses from 457 TSVIs. The results showed that TSVIs vary considerably in their preparation to teach writing and disagree as to whether writing instruction (above and beyond braille) is part of their responsibilities. Most TSVIs indicated that they believe writing to be important for their students with VI, and they reported using various writing practices in their instruction within different student groups.